Evaluating cross-cutting opportunities for dog-mediated rabies control: a scoping review - Tidman, R.; Larkins, A.; Auplish, A.; Benfield, C.; Cleaveland, S.; Fahrion, Anna S.; Leopardi, V.; Ghimire, R.; Morucci, K.; Sila, S.; Castillo-Neyra, R.; Okello, A. (Frontiers in Microbiology, 2025)
BackgroundDespite rabies being preventable, the disease continues to be under-prioritised and under-resourced, competing with other human and animal health diseases and socio-political agendas. The control of dog-mediated human rabies is a model of One Health operationalisation, and the One Health approach is core to the “Zero by 30” goal. There have been several opportunities proposed and/or piloted for the integration of rabies with other disease control efforts and interventions, in line with this One Health approach.MethodsA scoping review was conducted, following PRISMA guidelines, to summarise the nature and outcomes of cross-cutting approaches that have been applied to understand the opportunities available and evaluate the contexts in which such approaches can add value. Studies were included which demonstrated evidence describing an approach focused on dog-mediated rabies control and another health or development intervention affecting humans, animals, or the environment. In addition to the literature review, expert consultations were conducted to inform the development of recommended criteria or questions to consider when exploring cross-cutting or integrated approaches.ResultsRecords were mapped against the WHO NTD roadmap cross-cutting approach categories to help classify the evidence. Thirteen records in total were included in the review, with two of these records including aspects of multiple categories. Two records included evidence of planning and programme management; eleven records included evidence of activities or approaches associated with implementation and three records included evidence related to monitoring and evaluation, specifically surveillance. Insights from expert consultations complemented the available literature and led to the development of key criteria to consider when exploring cross-cutting approaches for rabies control.ConclusionIntegrated or cross-cutting approaches can offer the opportunity to enhance and build upon common and existing delivery platforms for health services and maximise the impact of limited resources. However, integrated approaches could have detrimental effects and their implementation requires careful consideration. Further evidence is needed to understand where cross-cutting approaches can be effective, sustainable, and scalable to support the agenda to end human deaths from dog-mediated rabies by 2030.